Konsep Implementasi Pembelajaran Pendidikan Agama Islam (PAI) di Tingkat Sekolah Dasar - Fiqra Nazib; Ayu Sri (PT. PENERBIT TIGA MUTIARA, 2024)
The formulation of the objectives of this research is: (1) to find out PAI learning planning at the Qorrota A'yun Integrated Islamic Elementary School (SDIT) and Al-Khoiriyyah Madrasah Ibtidaiyah (MI); (2) to determine the implementation of learning at the Qorrota A'yun (SDIT) and Al- (MI); (3) to find out the evaluation of learning at the Qorrota A'yun Integrated Islamic Elementary School (SDIT) and Al-Khoiriyyah Madrasah Ibtidaiyah (MI). The research method uses a qualitative approach while the subjects of this research are Islamic Religious Education (PAI) teachers, deputy head of curriculum and school principals at SDIT Qorrota A'yun and MI Al-Khoiriyyah. The results of this research are (1) Concept of Learning Planning for Islamic Religious Education (PAI) at SDIT Qurrota A'yun and MI Al-Khoiriyyah by first making a Learning Implementation Plan (RPP) according to the syllabus; (2) The implementation of PAI learning at SDIT Qurrota A'yun and MI Al-Khoiriyyah at SDIT Qurrota A'yun is held in two meetings a week, while at MI Al-Khoiriyyah it is held every day because PAI subjects are explained more specifically; (3) Evaluation of PAI learning at SDIT Qurrota A'yun and MI Al-Khoiriyyah carried out as in general schools with various written, oral and general practical tests.